PROSES PENCIPTAAN FILM DOKUMENTER TOPENG PANJI INDRAMAYU - Rina Yanti Harahap (Gelar : Jurnal Seni Budaya, 2014)
Indramayu Panji Mask is a mask dance greatly developed in West Java, especially Indramayu. Historically,people in Indramayu, for a long time, have used Indramayu Panji Mask as religious dance, entertainmentdance, and dance for wedding ceremony. The contribution of Indramayu Panji Mask in Indramayu is not onlyas an art aspect but also as social aspect, religious aspect, and the culture itself. Film “Topeng PanjiIndramayu is an important media to contribute Indramayu Panji Mask for people in Indramayu so that panjimask becomes the important part in the development of Indramayu culture. The documentary film is madethrough narrative approach that is a documentary form that uses speech act and the sources or the mainsubject to convey the content and message in the film to the audience.Keywords: Indramayu Panji Mask, documenter, culture